THE BATTLE BETWEEN ARJUNA AND KARNA IN MAHABHARATA COMICS BY R. A. KOSASIH AND KURUKSHETRA GAME: AN ADAPTATION STUDY - Krishnapatria, Kriswanda (Universitas Pendidikan Ganesha, 2017)
This paper examined an adaptation study of the longest Sanskrit epic, Mahabharata, from a novel by C. Rajagopalachari to comics by R. A. Kosasih and an online game named Kurukshetra by 7Seas Technologies Ltd. This paper only focused on the battle between Arjuna and Karna in Bharatayuddha War. This Great War, a conflict that arose from a dynastic succession struggle between two groups of cousins, the Kauravs and Pandavs for the throne of Hastinapura, lasted eighteen day taking place in the famous battlefield: Kurukshetra. The framework used to analyse the media was taken from books and lecture notes, and the theory used is based on Ellestrom of modalities by analyzing the element changes in the adaptation study. The conclusion is that both comics and game are adapted differently from the original novel. The findings also show how the comic and the game made few changes due to their different media nature and purposes.Â Key Words: Arjuna and Karna, Mahabharata comics, online game, Kurukshetra, adaptation study